LEGITIMASI KEKUASAAN DAN HUBUNGAN PENGUASA-RAKYAT DALAM PEMIKIRAN POLITIK SUKU DAYAK MA’ANYAN - Kisno Hadi (Universitas Gadjah Mada, 2018)
This article is a result of research on power legitimation and relation of rulers and people in political thought of Dayak Ma’anyan context. This Political thought was practiced by Nan Sarunai at the past centuries and inherited by some of people but the rest is disappeared. By the time of decentralization and the beginning of democration era at 1998, some of the concept was adopted like as on legitimating of power and relation between ruler and people in power. The implementation of the concept is seen in many ways e.g. in development of East Barito Regency which is believed as a continuation of Nan Sarunai Kingdom, the bestowal of past adat leader titles for regents or governors (dudus) and this ceremonial creating dependency relation between ruler and people which is people as the object. The aims of this research are to find out the thought and practice of power legitimation in the past and the implementation of power legitimation at present. Research use explanatory descriptive method and the data will analyze by interpretative descriptive. Research was held from April, 2014 to March, 2017 in community Dayak Ma’anyan in East Barito Regency, especially in Paju Epat District i.e Balawa, Murutuwu, Siong, and Telang. These villages believed still pratice and preserve adat of Nan Sarunai completely. Writer conduct deep interview with local adat leader i.e. Mantir, Damang, Pangulu Adat, and Pamakal. Use oral data likes Taliwakas (stories on leader), Hiyang Wadian (sacred song of priest which is sing in adat ritual), Sorosilah (histories of leader), and customary law of Dayak Ma’anyan. Data interpretation use Legitimacy Theory or religious legitimating of Franz Magnis Susesno and theory of relation between rulers – people from Soemarsaid Moertono.